Well‐Dispersed Ru‐Clusters Decorating Nanobox‐Structured CoP Synergistically Catalyze the NaBH4 Hydrolysis and Electro‐Reductive H2 Evolution. Issue 16 (26th June 2021) - Dou, Shasha; Hu, Chuan; Shi, Luyan; Zhang, Wanyu; Zhou, Shuqing; Yan, Puxuan; D'Souza, Lawrence; Isimjan, Tayirjan Taylor; Yang, Xiulin
Abstract: The high‐efficiency multifunctional materials have considerable significance in the area of sustainable energy to developing a cross‐usable and low‐cost catalyst. Nevertheless, substantial challenges are ahead on designing and synthesizing a high performance in a scalable and straightforward manner. Here, we have developed a novel bifunctional catalyst based on Ru/CoP nanoboxes (NBs) prepared using ZIF‐67 as a precursor. The nano hollow box structure and the strong electronic interaction between Ru clusters and CoP component are confirmed. The Ru/CoP NBs as a catalyst show excellent activities for catalytic NaBH4 hydrolysis such as high turnover frequency (1202.2 min −1 ), and small electrocatalytic H2 evolution overpotential (49 mV@10 mA cm −2 ) under ambient conditions. Besides, Ru/CoP NBs also display good stability and reusability. The excellent catalytic performance of Ru/CoP NBs is attributed to the synergy between Ru clusters and CoP species as well as the unique morphology that accelerates charge transfer, provides higher active surface area, and facilitates solute transport and gas emission. Abstract : Water splitting : A novel bifunctional Ru/CoP nanobox catalyst is fabricated by using ZIF‐67 as the precursor. The resulting Ru/CoP catalyst exhibits excellent activities for catalytic NaBH4 hydrolysis and electrocatalytic H2 evolution in alkaline media.